Seed germination of Solanum spp. (Solanaceae) for use in rehabilitation and commercial industries - Commander, L.; Merritt, D.; Rokich, D.; Flematti, G.; Dixon, Kingsley (CSIRO Publishing, 2008)
Effective methods for propagation of native Solanum species are required for mine rehabilitation and the native food industry in Australia. This study investigated seed germination of eight native Solanum species with respect to incubation temperature and the efficacy of germination-promoting compounds gibberellic acid (GA3), the butenolide isolated from smoke (karrikinolide, KAR1) and smoke water (SW). Seeds of all species were tested under a temperature regime of 26/13°C or 33/18°C. In these conditions, seeds of only two species, S. cunninghamii Benth. and S. phlomoides Benth. germinated to high levels without treatment. Of the remaining six species, GA3 alone promoted germination in S. chippendalei Symon, S. diversiflorum F.Muell. and S. sturtianum F.Muell., whereas GA3, KAR1 and SW were effective at promoting germination of S. centrale J.M.Black, S. dioicum W.Fitzg. and S. orbiculatum Dunal ex Poir. to varying degrees. Additional incubation temperatures (10, 15, 20, 25 and 30°C) were examined for S. centrale and S. orbiculatum. For both species, broadly similar patterns were noted in the response of seeds to GA3, KAR1 and SW across all temperatures. However, for S. centrale seeds, germination percentages were higher at 26/13°C than at any of the constant temperatures, and there was a trend of increasing germination with increasing constant temperature for S. orbiculatum seeds. Analysis of seed embryo type and imbibition characteristics and consideration of the subsequent germination results indicates that dormant Solanum seeds possess physiological dormancy. © CSIRO 2008.